OBSERVATIONS ON THE EMBRYONIC DEVELOPMENT OF FRESHWATER PULMONATE SNAIL LYMNAEA ACUMINATA (LAMARCK, 1822) (GASTROPODA: MOLLUSCA) - G. S. PANDE; M. U. PATIL; U. D. SHERKHANE (The Bioscan, 2010)
The freshwater pulmonate snails lay transparent gelatinous strips of eggs called egg masses or capsules. In the present study, a gross observation of embryonic development of L. acuminata was done. Early cleavages and subsequent various embryonic stages and time of appearance of different embryonic stages were recorded. The study revealed that the cleavage is spiral and holoblastic. After early cleavages followed the appearance of blastula, gastrula, trochophore stage, veliger stage, hippo stage ultimately resulting into hatching of fully developed young one on eleventh day. Many developmental characteristics observed are unique in molluscs. Various other characteristics of embryonic development in molluscs are also discussed.